2022
DOI: 10.1002/adsc.202200125
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Decarboxylative Coupling Between Allyl Carbonates and Vinyl Benzoxazinanones

Abstract: In the presence of Pd(OAc)2/biphenyl‐based phosphoramidite ligand(±)‐L4,the decarboxylative coupling of allyl carbonates with vinyl benzoxazinanonesoccurred readily, and deliveredthe desired productsin the acceptable chemical yields. The chemical structure of the obtained compounds was clearly identified by a single crystal X‐ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…As for these in situ generated reactive species, on the one hand, they can couple with themselves and 5 on the other hand, they are capable of cross-coupling. 6 On the basis of previous works on the synthetic methodologies of both benzofuran-based azadienes and allyl phenyl carbonates, we devised and explored novel decarboxylative 1,4-addition reactions between benzofuran-based azadienes 1 and allyl phenyl carbonates 2 (Scheme 1-3). To our delight, we found that the newly designed decarboxylative 1,4-addition reactions proceeded efficiently and delivered structurally new and highly functionalized benzofuran skeletons with potential bioactivities 7 in acceptable chemical yields.…”
Section: Introductionmentioning
confidence: 99%
“…As for these in situ generated reactive species, on the one hand, they can couple with themselves and 5 on the other hand, they are capable of cross-coupling. 6 On the basis of previous works on the synthetic methodologies of both benzofuran-based azadienes and allyl phenyl carbonates, we devised and explored novel decarboxylative 1,4-addition reactions between benzofuran-based azadienes 1 and allyl phenyl carbonates 2 (Scheme 1-3). To our delight, we found that the newly designed decarboxylative 1,4-addition reactions proceeded efficiently and delivered structurally new and highly functionalized benzofuran skeletons with potential bioactivities 7 in acceptable chemical yields.…”
Section: Introductionmentioning
confidence: 99%